Design and Development of Portable Pneumatic with Augmented Reality for Teaching and Learning Purposes - Mat Soad, Mariyati; Ibrahim, Hanizam; Ismail, Siti Hajar (Journal of Advanced Research in Applied Mechanics, 2020)
Immersive approach in learning pneumatic concepts help the learner understands better and retains information when ideas, and words are associated with images. Pneumatic is a power transferred system using compressed air and broadly uses in manufacturing meanwhile Augmented Reality, where the virtual reality added to the reality is an additional value in Beyond Education 4.0. A survey is conducted, and found that it is hard for student to understand the pneumatic systems with only displaying the figures of the circuit alone. This invention is to design and produce the portable training kit to facilitate lecturer to carry and explain about pneumatic circuit in the theory classes at any technical institutions. The body of the pneumatic components were designed and fabricated from the pallet wood. The recycle acrylic poster and screwed curtain rail were used as the board for pneumatic component circuit assembly. This board were attached to the box by the hinges, can fold and functioning as a top cover of the box too. For the Augmented Reality, students need to download the HP Reveal applications from the Play Store into their smart phone. They can scan 10 example of the circuits provided that will link to the learning videos of the real circuit. The result shows a small size and its 12 kg weight compared to the laboratory kits facilitate lecturers to carry into the theory classes. Using Augmented Reality, the teaching and learning session more interesting when students can choose the correct pneumatic component and construct the circuit by refer to the virtual reality in their smart phone.